ADITIVOS NO TRATAMENTO DOS DEJETOS FRESCOS DE POEDEIRAS COMERCIAIS - SANCHES, Danilo de Souza; GARCIA, Elis Regina de Moraes; SANTANA, Patrícia Gomes; ROCHA, Bruna de Jesus da; SILVA, Ademir Oliveira da; SILVA, Erick José Rosa da (ANAIS DO ENIC, 2018)
-